Analisis Literatur Tentang Penerapan Hukum Faraday Pada Transformator Listrik - Zega, Imjar Firlenta Jaya; Zalukhu, Trini Alfania (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Along with the quality of service that continues to increase from year to year, it is necessary to reanalyze (evaluation) to determine the condition and readiness of the equipment to maintain continuity and the electric power system in the process of sending the electric power. To maintain the continuity and reliability of theprocess of distributing electric power in the electric power system, therefore various protection systems are needed from disturbances that may arise.20 kV distribution network on a transformer 30 MVA TFT 1 70/20 kV 30 MVA using a safety system Ground Fault Relay (GFR) that is used to detect the smallest current.. This study uses a Neutral Grounding Resistor (NGR) and solid neutral grounding system to determine the proper setting of the GFR while the single-phase short circuit to ground fault occurs and to determine the effect of relay adjustment when using a neutral grounding system by simulating ETAP 12.6. The maximum fault current of a single- phase short circuit with the direct grounding method is 1.15 kA, while the maximum fault current with the NGR grounding method is 0.235 kA. At the Bolok – Tenau III connection, the relay working time setting obtained from the solid grounding system is 0.5 s, and the relay working time setting obtained from the NGR grounding system is 0.5. In this case, the grounding method using a Neutral Grounding Resistor is more effective for neutral grounding of the transformer because it can reduce the short circuit current that occurs so that it does not endanger humans or nearby equipment.